Pengaruh Pengungkapan Corporate Social Responsibility Dan Kinerja Keuangan Perusahaan Terhadap Return Saham Perusahaan di Indeks LQ45 Bursa Efek Indonesia Periode 2008-2010 - Tomas Setya Wahyu Budi; Atim Djazuli (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research investigates the effect of corporate social responsibility disclosure and firm financial performance of stock return by analyzed the performance on the companies that have made the disclosure of corporate social responsibility and corporate performance reports disclose in its annual report. The research was conducted at the companies that listed in the LQ45 Index of Indonesia Stock Exchange. The data that was analyzed is an quantitative data in the form of time series in 2008-2010. Those quantitative data in the form was such as calculation of stock return, calculation of Corporate Social Responsibility Disclosure (CSRDi), as well as the firm’s financial performance (NPM, ROA, EPS, PER). Data analysis using descriptive analysis, multiple linear regression analysis, and statistical tests. There are findings in this study that the effect of the simultaneous of Corporate Social Responsibility disclosure as measured by the Index of Corporate Social Responsibility Disclosure and Firm Financial Performance is measured by the NPM, ROA, EPS and PER have a positive influence on stock returns of listed companies in the LQ45 index IDX. The following variables in partially test, Corporate Social Responsibility Disclosure, Return On Asetss (ROA), Earning Per Share (EPS) have a positive effect on stock prices of listed companies in the LQ45 index IDX. Keywords: Stock Return, Corporate Social Responsibility, Firms Financial Performance